Flexible Luminescent Organic Bulk Crystal: 2D Elasticity toward 3D Optical Waveguide. Issue 22 (1st September 2019) - Huang, Rui; Tang, Baolei; Ye, Kaiqi; Wang, Chenguang; Zhang, Hongyu
Abstract: The study of elastic organic single crystals becomes a hot research field in the crystal engineering, and elastic bending of needle‐like crystals has been carefully investigated recently. Herein, based on a structurally simple molecule dimethyl 2, 5‐diaminoterephthalate (DMDAT), the organic crystals which display not only elastic bending ability but also elastic twisting ability under applied stress are reported. These ribbon‐like DMDAT crystals are fully flexible and can be freely bended and twisted, thus forming any 3D conformation. Moreover, the unique X‐shaped tetrasubstituted benzene structure enables DMDAT crystals to display efficient yellow emission based on a very small π‐system. Taking these advantages, 3D optical waveguide is successfully realized in the DMDAT crystal with a highly twisted 3D belt‐shaped structure, demonstrating the ultimate 3D application of flexible organic bulk crystals. Abstract : The fully flexible organic bulk crystals, which can be elastically bended as well as twisted, are prepared by crystallization of the structurally simple fluorophore dimethyl 2, 5‐diaminoterephthalate. Employing the crystal with a highly bended and twisted conformation, 3D optical waveguide is successfully realized.